Satisfacción de pacientes con los servicios de telemedicina en la Atención Primaria. Guano, 2021. - Gualle Godoy, Jorge Andrés (2022)
ABSTRACT: Telemedicine is the application of information and communication technologies in conjunction with medicine. Its development began in the twentieth century. Its greatest boom in prevention, diagnosis and disease control occurred during the Covid 19 pandemic. Medical practice has questioned the complexity of physical contact, a situation that affects the doctor-patient relationship leading to misdiagnosis or unsatisfactory treatment, hence the importance of studying the impact on users in primary health care. This project aims to determine the level of satisfaction of telemedicine services in a pandemic in terms of the patient-health personnel relationship in primary health care, Guano health center, 2021. The Centro de Salud Guano health personnel corresponds to the first level of care of the Ministry of Public Health (MSP), with a total universe of 208 health professionals who were part of the population and sample. The information responds to a specific period and places in a study with a qualitative approach, cross-sectional, descriptive, and exploratory research level. Two questionnaires were applied to collect information, an adaptation of the Barker questionnaire consisting of 15 questions with a score option on five levels of satisfaction. Despite being the first time they have used this tool, there is evidence of satisfaction with the ease of the means used to access, request, and receive medical care. For health workers, it permits promoting access to health care, reaching a larger population with timely diagnoses, as well as an incentive for professional development. It is concluded that teleconsultation through video-call permits capturing sounds and images in real-time, preserving the principles of medical ethics in the health personnel-patient relationship, which undergoes an adaptive change. The viability of the permanent application of telemedicine in primary health care has been found to be a tool of new scope in prevention, diagnosis, and timely treatment, the lack of empathy for the population, is evident, which is a setback to the digital era in conjunction with medicine, since the level of satisfaction is neutral, giving rise to new research topics, thus improving the teleconsultation in our health system. Keywords: Telemedicine, Satisfaction, Centro de Salud Guano, Health Personnel. Reviewed by: Mgs. Lorena Solís Viteri ENGLISH PROFESSOR c.c. 0603356783